Reinforcing steel bar sleeve grouting material for high-strength micro-expansion assembly type concrete structure
Through the combination of scientific proportioning and functional admixtures, a high-strength, micro-expanded steel sleeve grouting material was developed, which solved the shortcomings of existing grouting materials in terms of high strength and micro-expandability, achieved the combination of high strength and micro-expanding performance, and met the strict requirements of prefabricated buildings.
Patent Information
- Application Number
- CN202411811448.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-28
AI Technical Summary
The existing reinforced sleeve grouting material has shortcomings in terms of high strength and micro-expansion, which is difficult to meet the strict requirements for connecting joints in prefabricated buildings.
Through scientific material ratio and functional admixture, a high-strength slightly expanded steel sleeve grouting material is developed. The specific formula includes cement, silicon fume, lithium slag powder, magnesium slag powder, quartz sand, basalt sand, etc., and water reducing agent, retarder, reinforcement, defoaming agent, suspension stabilizer, plastic expansion agent and UEA expansion agent are added.
The perfect combination of high strength and micro-expansion properties of grouting materials is achieved, ensuring good flowability and compactness during construction, and meeting the strict requirements for connecting joints in prefabricated buildings.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a steel sleeve grouting material for a high-strength micro-expansion assembled concrete structure. Background Art
[0002] With the continuous development of modern construction technology, prefabricated concrete structures have gradually become an important development direction of the construction industry due to their high efficiency, environmental protection and energy saving. However, the core of prefabricated concrete structures lies in the effective connection between prefabricated components, especially the steel sleeve grouting connection technology, whose performance is directly related to the safety and durability of the overall structure.
[0003] At present, most common grouting materials on the market are mainly cement-based materials, which are prepared by adding appropriate amounts of fine aggregates, admixtures, etc. However, these grouting materials are often difficult to achieve ideal conditions in terms of strength, shrinkage, etc. In addition, with the widespread application of prefabricated buildings, the performance requirements for grouting materials are also increasing, especially in complex structures such as high-rise and large-span structures, which put forward more stringent standards for the strength and shrinkage of grouting materials.
[0004] Although traditional steel sleeve grouting materials meet the connection requirements to a certain extent, they are still insufficient in terms of high strength and micro-expansion. High strength ensures the stability of the connection joint under complex stress conditions, while micro-expansion avoids cracks and performance degradation caused by changes in material volume during the grouting process. Therefore, it is particularly important to develop a steel sleeve grouting material that has both high strength and micro-expansion. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-strength and micro-expansion steel sleeve grouting material for assembled concrete structures, which achieves high-strength and micro-expansion effects through scientific material ratios and functional admixtures, thereby overcoming the defects of traditional grouting materials.
[0006] The present invention adopts the following technical solutions.
[0007] A steel sleeve grouting material for a high-strength, slightly expansive assembled concrete structure, comprising the following raw materials in parts by weight: 735-795 parts of cement, 15-85 parts of silica fume, 80-90 parts of lithium slag powder, 9-36 parts of magnesium slag powder, 500-800 parts of quartz sand, 100-400 parts of basalt sand, 9-12.6 parts of water reducer, 0.9-4.5 parts of retarder, 0.9-4.5 parts of reinforcing agent, 0.6-1.2 parts of defoamer, 0.6-1.2 parts of suspension stabilizer, 0.1-0.3 parts of plastic expansion agent, and 45-72 parts of UEA expansion agent; The cement is ordinary Portland cement, model P·O 52.5R; The enhancer consists of triisopropanolamine and triethanolamine; The water reducing agent is selected from powdered solid polycarboxylic acid water reducing agent; The enhancer consists of triisopropanolamine and triethanolamine.
[0008] The silica fume is densified silica fume.
[0009] Preferably, the silica fume has a bulk density of ≥350 kg / m³, a SiO2 content of ≥90%, a moisture content of ≤2%, a loss on ignition of ≤3%, a water requirement ratio of ≤125%, an activity index of ≥105%, and a radioactivity I Ra ≤1.0,Ir≤1.0.
[0010] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown micro powder.
[0011] Preferably, the density of the lithium slag powder is ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0012] The magnesium slag powder is the waste slag discharged after the magnesium metal factory adopts the "Pidgeon method" to refine magnesium metal, and is dried and ground into a gray-white powder.
[0013] Preferably, the magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0014] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0015] The basalt sand is obtained by jaw crushing of massive basalt.
[0016] Preferably, the basalt sand has a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0017] The water reducing agent has a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0018] Preferably, the water reducing agent is a powder solid polycarboxylic acid-based high performance water reducing agent.
[0019] The retarder is brown-yellow powder calcium lignin sulfonate.
[0020] Preferably, the insoluble matter of calcium lignin sulfonate is ≤0.5%, the lignin content is ≥50%, the pH (20°C aqueous solution) is 4.0-6.0, and the moisture content is ≤8%.
[0021] Preferably, the enhancer is composed of triisopropanolamine and triethanolamine in a weight ratio of 3:1.
[0022] The defoamer is an organosilicon defoamer.
[0023] Preferably, the defoaming agent is hydroxypropyl dimethicone.
[0024] The suspension stabilizer is a mixture of polyaluminium ferric chloride, silicon dioxide and attapulgite.
[0025] The preferred polyaluminium ferric chloride is a brown powder with a mesh size of 300; the silicon dioxide is a white powder produced by a gas phase process with a particle size of 7-40nm, a silicon dioxide content of ≥95%, and a specific surface area of 100-400m 2 / g; attapulgite is in the form of needles, fibers, rods, or fiber aggregate powders; it is composed of polyaluminium ferric chloride, silicon dioxide, and attapulgite in a weight ratio of 9:2:9.
[0026] The plastic expansion agent is yellow powder, which is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide.
[0027] Preferably, the plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, glyceryl stearate, potassium hydroxide, diatomaceous earth and calcium oxide in a weight ratio of 4:1:5:60:30.
[0028] The UEA expansion agent consists of calcium sulfoaluminate, aluminum sulfate, aluminum oxide and calcium silicate.
[0029] Preferably, the UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate in a weight ratio of 160:30:9:1.
[0030] Beneficial effects of the present invention: The present invention proposes a high-strength and micro-expansion steel sleeve grouting material for prefabricated concrete structures. The grouting material is designed to achieve a perfect combination of high strength and micro-expansion by scientifically proportioning a variety of raw materials, including high-quality cement, fine aggregate, and a variety of functional admixtures. By optimizing the formula design, it is ensured that the grouting material has good fluidity, compressive strength, and durability, meeting the strict requirements of prefabricated buildings for connection joints.
[0031] The present invention clarifies different components of solid waste lithium slag-silica fume-based grouting material and the addition amounts of different components, so that the obtained grouting material has good fluidity, strength and micro-expansion. The grouting material of the present invention can penetrate into small gaps, has good density, and good fluidity ensures its construction; silica fume and lithium slag powder are used as active admixtures in the grouting material to reduce the amount of cement and delay the heat release of cement hydration. At the same time, calcium lignin sulfonate is used as a retarder to prolong the setting time, reduce the fluidity loss, and facilitate construction. Silicon aluminum oxides in silica ash and lithium slag powder participate in secondary hydration reaction to generate CSH gel. At the same time, under the stimulation of triisopropanolamine and triethanolamine, silica ash and lithium slag powder participate in hydration reaction to form gel hardening, which improves strength, improves pore structure and durability. The calcium sulfate component contained in the lithium slag powder reduces the amount of cement and the hydration product plays a role of micro-expansion compensating shrinkage. At the same time, the magnesium slag powder contains CaO and MgO to produce an expansion effect to further compensate for the shrinkage. The grouting material of the present invention has high strength and micro-expansion performance, does not bleed water, does not separate, and meets the requirements of prefabricated building construction. DETAILED DESCRIPTION
[0032] The specific implementation of the present invention is further described below in conjunction with specific examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and the protection scope of the present invention is not limited to the examples of the present invention. Example 1
[0033] A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 735 parts of cement, 85 parts of silica fume, 80 parts of lithium slag powder, 36 parts of magnesium slag powder, 500 parts of quartz sand, 400 parts of basalt sand, 9 parts of water reducer, 4.5 parts of retarder, 0.9 parts of enhancer, 1.2 parts of defoamer, 0.6 parts of suspension stabilizer, 0.3 parts of plastic expansion agent and 45 parts of UEA expansion agent.
[0034] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0035] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0036] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity IRa ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0037] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0038] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0039] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0040] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0041] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0042] The reinforcing agent is composed of triisopropanolamine and triethanolamine, and the weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0043] The defoamer is an organosilicon defoamer.
[0044] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0045] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0046] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0047] Example 2 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 795 parts of cement, 15 parts of silica fume, 90 parts of lithium slag powder, 9 parts of magnesium slag powder, 800 parts of quartz sand, 100 parts of basalt sand, 12.6 parts of water reducer, 0.9 parts of retarder, 4.5 parts of enhancer, 0.6 parts of defoamer, 1.2 parts of suspension stabilizer, 0.1 parts of plastic expansion agent, and 72 parts of UEA expansion agent.
[0048] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0049] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0050] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0051] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0052] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0053] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0054] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0055] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0056] The reinforcing agent is composed of triisopropanolamine and triethanolamine, and the weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0057] The defoamer is an organosilicon defoamer.
[0058] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0059] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0060] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0061] Example 3 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 765 parts of cement, 50 parts of silica fume, 85 parts of lithium slag powder, 22.5 parts of magnesium slag powder, 650 parts of quartz sand, 250 parts of basalt sand, 10.8 parts of water reducer, 2.7 parts of retarder, 2.7 parts of enhancer, 0.9 parts of defoamer, 0.9 parts of suspension stabilizer, 0.2 parts of plastic expansion agent and 58.5 parts of UEA expansion agent.
[0062] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0063] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0064] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0065] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0066] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0067] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0068] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0069] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0070] The reinforcing agent is composed of triisopropanolamine and triethanolamine, and the weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0071] The defoamer is an organosilicon defoamer.
[0072] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0073] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0074] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0075] Example 4 745 parts of cement, 75 parts of silica fume, 80 parts of lithium slag powder, 27 parts of magnesium slag powder, 600 parts of quartz sand, 300 parts of basalt sand, 9 parts of water reducer, 3.6 parts of retarder, 1.8 parts of enhancer, 1.2 parts of defoamer, 0.6 parts of suspension stabilizer, 0.3 parts of plastic expansion agent, and 54 parts of UEA expansion agent.
[0076] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0077] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0078] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0079] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0080] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0081] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0082] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0083] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0084] The reinforcing agent is composed of triisopropanolamine and triethanolamine, and the weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0085] The defoamer is an organosilicon defoamer.
[0086] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0087] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0088] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0089] Example 5 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 775 parts of cement, 35 parts of silica fume, 90 parts of lithium slag powder, 18 parts of magnesium slag powder, 700 parts of quartz sand, 200 parts of basalt sand, 12.6 parts of water reducer, 1.8 parts of retarder, 3.6 parts of enhancer, 0.6 parts of defoamer, 1.2 parts of suspension stabilizer, 0.1 parts of plastic expansion agent, and 63 parts of UEA expansion agent.
[0090] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0091] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0092] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0093] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0094] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0095] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0096] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0097] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0098] The reinforcing agent is composed of triisopropanolamine and triethanolamine, and the weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0099] The defoamer is an organosilicon defoamer.
[0100] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0101] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0102] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0103] Comparative Example 1 A steel sleeve grouting material for a high-strength, slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 900 parts of cement, 22.5 parts of magnesium slag powder, 650 parts of quartz sand, 250 parts of basalt sand, 10.8 parts of water reducing agent, 2.7 parts of retarder, 2.7 parts of reinforcing agent, 0.9 parts of defoaming agent, 0.9 parts of suspension stabilizer, 0.2 parts of plastic expansion agent, and 58.5 parts of UEA expansion agent.
[0104] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0105] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0106] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0107] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0108] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0109] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0110] The reinforcing agent is composed of triisopropanolamine and triethanolamine, and the weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0111] The defoamer is an organosilicon defoamer.
[0112] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0113] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0114] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0115] Comparative Example 2 A steel sleeve grouting material for a high-strength, slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 855 parts of cement, 45 parts of silica fume, 22.5 parts of magnesium slag powder, 650 parts of quartz sand, 250 parts of basalt sand, 10.8 parts of water reducer, 2.7 parts of retarder, 2.7 parts of enhancer, 0.9 parts of defoamer, 0.9 parts of suspension stabilizer, 0.2 parts of plastic expansion agent, and 58.5 parts of UEA expansion agent.
[0116] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0117] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0118] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0119] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0120] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0121] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0122] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0123] The enhancer is composed of triisopropanolamine and triethanolamine.
[0124] The defoamer is an organosilicon defoamer. The weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0125] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0126] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0127] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0128] Comparative Example 3 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 810 parts of cement, 45 parts of silica fume, 45 parts of lithium slag powder, 22.5 parts of magnesium slag powder, 650 parts of quartz sand, 250 parts of basalt sand, 10.8 parts of water reducer, 2.7 parts of retarder, 2.7 parts of enhancer, 0.9 parts of defoamer, 0.9 parts of suspension stabilizer, 0.2 parts of plastic expansion agent, and 58.5 parts of UEA expansion agent.
[0129] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0130] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0131] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0132] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0133] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0134] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0135] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0136] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0137] The reinforcing agent is composed of triisopropanolamine and triethanolamine, and the weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0138] The defoamer is an organosilicon defoamer.
[0139] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0140] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0141] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0142] Comparative Example 4 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 775 parts of cement, 35 parts of silica fume, 90 parts of lithium slag powder, 18 parts of magnesium slag powder, 700 parts of quartz sand, 200 parts of basalt sand, 12.6 parts of water reducing agent, 0.6 parts of defoaming agent, 1.2 parts of suspension stabilizer, 0.1 parts of plastic expansion agent, and 63 parts of UEA expansion agent.
[0143] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0144] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0145] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0146] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0147] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0148] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0149] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0150] The defoamer is an organosilicon defoamer.
[0151] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0152] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0153] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0154] Comparative Example 5 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 775 parts of cement, 35 parts of silica fume, 90 parts of lithium slag powder, 18 parts of magnesium slag powder, 700 parts of quartz sand, 200 parts of basalt sand, 12.6 parts of water reducer, 1.8 parts of retarder, 0.6 parts of defoamer, 1.2 parts of suspension stabilizer, 0.1 parts of plastic expansion agent, and 63 parts of UEA expansion agent.
[0155] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0156] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0157] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0158] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0159] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0160] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0161] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0162] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0163] The defoamer is an organosilicon defoamer.
[0164] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0165] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0166] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0167] Comparative Example 6 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 775 parts of cement, 35 parts of silica fume, 90 parts of lithium slag powder, 18 parts of magnesium slag powder, 700 parts of quartz sand, 200 parts of basalt sand, 12.6 parts of water reducer, 3.6 parts of enhancer, 0.6 parts of defoamer, 1.2 parts of suspension stabilizer, 0.1 parts of plastic expansion agent, and 63 parts of UEA expansion agent.
[0168] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0169] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0170] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0171] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0172] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0173] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0174] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0175] The reinforcing agent is composed of triisopropanolamine and triethanolamine, and the weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0176] The defoamer is an organosilicon defoamer.
[0177] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0178] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0179] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0180] Comparative Example 7 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 775 parts of cement, 35 parts of silica fume, 90 parts of lithium slag powder, 18 parts of magnesium slag powder, 700 parts of quartz sand, 200 parts of basalt sand, 12.6 parts of water reducer, 1.8 parts of retarder, 3.6 parts of enhancer, 0.6 parts of defoamer, 1.2 parts of suspension stabilizer, 0.1 parts of plastic expansion agent, and 63 parts of UEA expansion agent.
[0181] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0182] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0183] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0184] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0185] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0186] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0187] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0188] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0189] The reinforcing agent is triisopropanolamine.
[0190] The defoamer is an organosilicon defoamer.
[0191] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0192] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0193] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0194] Comparative Example 8 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 775 parts of cement, 35 parts of silica fume, 90 parts of lithium slag powder, 18 parts of magnesium slag powder, 700 parts of quartz sand, 200 parts of basalt sand, 12.6 parts of water reducer, 1.8 parts of retarder, 3.6 parts of enhancer, 0.6 parts of defoamer, 1.2 parts of suspension stabilizer, 0.1 parts of plastic expansion agent, and 63 parts of UEA expansion agent.
[0195] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0196] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0197] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0198] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0199] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0200] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0201] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0202] The retarder is brown-yellow powder calcium lignin sulfonate, with insoluble matter ≤0.5%, lignin content ≥50%, pH (20°C aqueous solution) 4.0-6.0, and moisture ≤8%.
[0203] The enhancer is triethanolamine.
[0204] The defoamer is an organosilicon defoamer.
[0205] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0206] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0207] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0208] Comparative Example 9 A steel sleeve grouting material for a high-strength slightly expansive assembled concrete structure is composed of the following raw materials in parts by weight: 735 parts of cement, 85 parts of silica fume, 80 parts of lithium slag powder, 36 parts of magnesium slag powder, 500 parts of quartz sand, 400 parts of basalt sand, 9 parts of water reducer, 4.5 parts of retarder, 0.9 parts of enhancer, 1.2 parts of defoamer, 0.6 parts of suspension stabilizer, 0.3 parts of plastic expansion agent and 45 parts of UEA expansion agent.
[0209] The cement is ordinary Portland cement, and the model is P·O 52.5R.
[0210] The silica fume is densified silica fume, which satisfies the following conditions: bulk density ≥350kg / m³, SiO2 content ≥90%, water content ≤2%, loss on ignition ≤3%, water requirement ratio ≤125%, activity index ≥105%, radioactivity IRa ≤1.0, and Ir ≤1.0.
[0211] The lithium slag powder is produced by the sulfuric acid process to produce lithium carbonate, and is dried and ground into a yellow-brown fine powder, satisfying the lithium slag powder density of ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
[0212] The magnesium slag powder is the waste slag discharged after the magnesium metal factory uses the "Pijeng method" to refine magnesium metal. It is dried and ground into fine gray powder. The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
[0213] The quartz sand is quartz particles processed after quartz stone is crushed, and the particle size is 20-40 meshes.
[0214] The basalt sand is made from massive basalt by jaw crushing, with a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
[0215] The water reducing agent is a polycarboxylic acid solid powder water reducing agent with a water reducing rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
[0216] The retarder is sodium gluconate.
[0217] The reinforcing agent is composed of triisopropanolamine and triethanolamine, and the weight ratio of triisopropanolamine to triethanolamine is 3:1.
[0218] The defoamer is an organosilicon defoamer.
[0219] The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite, and the weight ratio of polyaluminium ferric chloride, silicon dioxide and attapulgite is 9:2:9.
[0220] The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide. The weight ratio of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide is 4:1:5:60:30.
[0221] The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate, wherein the weight ratio of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate is 160:30:9:1.
[0222] Performance Testing Test method: The water-to-binder ratio of this grouting material is 0.24. The experimental operation steps are carried out in accordance with JG / T 408-2019 "Sleeve Grouting Material for Rebar Connection". The fluidity, vertical expansion rate, and 1d, 3d, and 28d compressive strength of the grouting material are tested. The results are shown in Table 1 below.
[0223] Table 1 Grouting material performance test results
[0224] By comparing Example 3 with Comparative Examples 1, 2 and 3 in Table 1, it can be seen that when silica fume and lithium slag powder are added to the grouting material, the early strength decreases due to the increase in the amount of silica fume-lithium slag powder added, and the silica fume-lithium slag powder can improve the later strength of the grouting material, playing a synergistic role in promoting strength development.
[0225] Comparing Example 5 with Comparative Examples 4, 5, 6, 7 and 8, it can be seen that retarders and enhancers are indispensable for solid waste-doped grouting materials, and retarders are beneficial to the flow of grouting materials and reduce fluidity loss.
[0226] Compared with Example 5, the composite activator of Comparative Examples 7 and 8 can achieve complementary advantages. Compared with the single addition of triisopropanolamine or triethanolamine, the stimulating effect on the solid waste admixture is stronger. Triisopropanolamine can promote the hydration reaction to increase the CH concentration and form a lubricating film in the admixture to improve fluidity and mineral dispersion, thereby promoting the participation of active silicon aluminum oxide in the hydration reaction to improve the strength, especially the late strength. Triethanolamine can disintegrate and hydrate the active substance under the chelation effect, thereby earlier hydration reaction is beneficial to the early strength development. Mixing the two as an activator can achieve the effect of complementary advantages.
[0227] Comparison of Example 9 using sodium gluconate as a retarder with Example 1 shows that the retarding effect of calcium lignin sulfonate at the same dosage is stronger than that of sodium gluconate, the fluidity loss is reduced, and it is beneficial to improve the density and strength. The later compressive strength of the grouting material is greater than that of Comparative Example 9.
Claims
1. A steel sleeve grouting material for high-strength micro-expansion assembled concrete structure, characterized in that: The invention is composed of the following raw materials in parts by weight: 735-795 parts of cement, 15-85 parts of silica fume, 80-90 parts of lithium slag powder, 9-36 parts of magnesium slag powder, 500-800 parts of quartz sand, 100-400 parts of basalt sand, 9-12.6 parts of water reducing agent, 0.9-4.5 parts of retarder, 0.9-4.5 parts of reinforcing agent, 0.6-1.2 parts of defoaming agent, 0.6-1.2 parts of suspension stabilizer, 0.1-0.3 parts of plastic expansion agent, and 45-72 parts of UEA expansion agent; The cement is selected from ordinary Portland cement, model P·O52.5R; The enhancer consists of triisopropanolamine and triethanolamine; The water reducing agent is selected from powdered solid polycarboxylic acid water reducing agent; The retarder is calcium lignin sulfonate.
2. The high-strength micro-expansion steel sleeve grouting material for assembled concrete structure according to claim 1 is characterized in that: The silica fume is selected from densified silica fume, with a bulk density of ≥350kg / m³, a SiO2 content of ≥90%, a moisture content of ≤2%, a loss on ignition of ≤3%, a water requirement ratio of ≤125%, an activity index of ≥105%, and a radioactive I Ra ≤1.0,Ir≤1.
0.
3. The high-strength, slightly expansive steel sleeve grouting material for assembled concrete structure according to claim 1, characterized in that: The lithium slag powder density is ≥2.4g / cm 3 , specific surface area ≥800m 2 / kg, moisture content ≤1.5%, sulfur trioxide content ≤8%, water requirement ratio ≤115%, 7d activity index ≥70%, 28d activity index ≥95%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%, water immersion stability qualified.
4. The high-strength, slightly expansive steel sleeve grouting material for assembled concrete structures according to claim 1, characterized in that: The magnesium slag powder has a 45um sieve residue of ≤12% and a specific surface area of ≥400m 2 / kg, water content ≤ 1%, radioactivity I Ra ≤1.0, Ir≤1.0, chloride ion content≤0.06%.
5. The high-strength, slightly expansive steel sleeve grouting material for assembled concrete structure according to claim 1, characterized in that: The quartz sand has a specification of 20-40 mesh; the basalt sand has a particle size of 0.5-2 mm and a specific gravity of ≥2.8 g / cm 3 , bulk density ≥1.8g / cm 3 , Mohs hardness ≥7.
6. The high-strength, slightly expansive steel sleeve grouting material for assembled concrete structures according to claim 1, characterized in that: The powdered solid polycarboxylic acid-based water reducer has a water reduction rate of ≥30%, no water seepage, and an initial setting time and a final setting time of ≥2h.
7. The high-strength, slightly expansive steel sleeve grouting material for assembled concrete structures according to claim 1, characterized in that: The calcium lignin sulfonate has an insoluble matter of ≤0.5%, a lignin content of ≥50%, a pH value of 4.0-6.0 in a 20° C. aqueous solution, and a moisture content of ≤8%.
8. The high-strength micro-expansion steel sleeve grouting material for assembled concrete structure according to claim 1, Characterized in that the enhancer is composed of triisopropanolamine and triethanolamine in a weight ratio of 3:1; The defoamer is an organosilicon defoamer; The suspension stabilizer is composed of polyaluminium ferric chloride, silicon dioxide and attapulgite in a weight ratio of 9:2:
9.
9. The high-strength, slightly expansive steel sleeve grouting material for assembled concrete structure according to claim 1, characterized in that: The plastic expansion agent is composed of p-nitrobenzene diazonium fluoroborate, stearic acid glyceryl ester, potassium hydroxide, diatomaceous earth and calcium oxide in a weight ratio of 4:1:5:60:
30.
10. The steel sleeve grouting material for high-strength and slightly expansive assembled concrete structure according to claim 1, characterized in that: The UEA expansion agent is composed of calcium sulfoaluminate, aluminum sulfate, aluminum oxide, and calcium silicate in a weight ratio of 160:30:9:1.
Citation Information
Cited By
Low-alkalinity and early-strength ardealite filling curing material and preparation method thereof
CN119751012A